2007
DOI: 10.1063/1.2768534
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio energies of nonconducting crystals by systematic fragmentation

Abstract: A systematic method for approximating the ab initio electronic energy of molecules from the energies of molecular fragments has been adapted to estimate the total electronic energy of crystal lattices. The fragmentation method can be employed with any ab initio electronic structure method and allows optimization of the crystal structure based on ab initio gradients. The method is demonstrated on SiO(2) polymorphs using the Hartree-Fock approximation, second order Moller-Plesset perturbation theory, and the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 15 publications
3
103
0
Order By: Relevance
“…This is in agreement with the solid-state 13 C NMR experiments, which suggest that the AAP and AEP functionalities remain rigid on the NMR time scale (in this case sub-millisecond), whereas the CP substituent executes faster motions. These conformations are most likely governed by the hydrogen bonds between the amine moieties of the functional groups and the silanol groups on the silica surface.…”
Section: Introductionsupporting
confidence: 80%
“…This is in agreement with the solid-state 13 C NMR experiments, which suggest that the AAP and AEP functionalities remain rigid on the NMR time scale (in this case sub-millisecond), whereas the CP substituent executes faster motions. These conformations are most likely governed by the hydrogen bonds between the amine moieties of the functional groups and the silanol groups on the silica surface.…”
Section: Introductionsupporting
confidence: 80%
“…The SFM has been used to study small-and medium-sized organic molecules, 35 as well as crystals. 37 In this paper, it was demonstrated that the SFM, when using EFPs for the nonbonded interactions, has a mean averaged error of 1.8 kcal/mol for several R-helical isomers at the HF/ 6-31++G (d,p) level of theory. The SFM is formally independent of the ab initio methods used in calculations of the fragments, thereby facilitating highly accurate energies and relative energies with nearly linear scaling as the size of the system is increased.…”
Section: Discussionmentioning
confidence: 99%
“…These nonbonded interactions are naturally incorporated into the full ab initio calculation. The nonbonded interactions are modeled within the SFM framework by using a modified many-body expansion; 37 this expansion relies on the assumption that bonded interactions are much stronger than nonbonded ones.…”
Section: The Systematic Fragmentation Methods (Sfm)mentioning
confidence: 99%
See 2 more Smart Citations